INNOVATION OF ORGANIC YELLOW PUMPKIN BROWNIES WITH A MIXTURE OF GINGER AND CINNAMON HERBAL INFUSED AS A BUSINESS OPPORTUNITY IN THE HEALTHY FOOD INDUSTRY - Linda Farikhatul Muti'; Dyan Naffisa Prissilawaty; Kharis Fadlullah Hana (Syarif Hidayatullah State Islamic University Jakarta, 2025)
This research aims to develop healthy food product innovations in the form of organic yellow pumpkin brownies with the addition of herbal infused ginger and cinnamon. This innovation comes as a response to the increasing trend of healthy food consumption and the need for functional snacks made from local. The method used is Research and Development (R&D) with six stages, including problem collection, data collection, product design, validation, trial, and product revision. The main ingredients in this product include yellow squash, ginger, and cinnamon which are known to have health benefits, such as boosting immunity and metabolism. The validation results by informants (nutrition students, biology, MSME actors, and potential consumers) showed a positive response to the taste, texture, and health benefits of the product. Some suggestions for improvement are given regarding the use of healthier substitutes, such as stevia and gluten-free flour. Product trials show that consumers love the distinctive taste of brownies with a spicy aroma and eco-friendly packaging. This product has the potential to be an innovative healthy snack, as well as a promising business opportunity in the local ingredient-based healthy food industry. By carrying the concept of sustainability, this product is expected to be an alternative solution to functional food that supports a healthy lifestyle.